Contemporary Management of Bell Palsy - Jowett, Nate; Hadlock, Tessa A. (Facial Plastic Surgery, 2015)
Bell palsy (BP) is the most common diagnosis in acute and chronic facial palsy. Although most patients fully recover, more than one-quarter will have residual dysfunction. Of these, nearly half will demonstrate severe limitations in facial expression. Though significant attention has been paid to acute management and prognosis, a paucity of literature exists addressing management of the long-term sequelae of BP. This article describes contemporary use of physical therapy, injectables, and static and dynamic surgical procedures in facial reanimation of acute and chronic BP.
Keywords: Bell palsy; facial reanimation; synkinesis; facial paralysis; facial palsy